2016
DOI: 10.4103/0019-5545.191995
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric morbidity among cancer patients – hospital-based, cross-sectional survey

Abstract: Aim:To study the prevalence of Psychiatric disorders in cancer patients and to find out the factors associated with Psychiatric disorders in Cancer Patients.Settings and Design:Department of Radiotherapy, Medical College, Thiruvananthapuram, cross sectional survey design was used.Methods and Material:Adult patients (18 years of age and above), having a diagnosis of carcinoma were selected by consecutive sampling method.A questionnaire which included back ground data, socio economic variables, treatment variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Globally, now, about one out of six deaths are due to cancer. The cancer deaths worldwide are projected to reach over 11 million people by 2030 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, now, about one out of six deaths are due to cancer. The cancer deaths worldwide are projected to reach over 11 million people by 2030 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to cure the condition systematically, it is necessary to acquire perception into the prevalence, severity, direction of the psychological abnormality and the factors affecting them. (2) Cancer sufferers must face assorted strain and elements which cause their psychosomatic anguish, principally apprehension and melancholy. (4) These may affect the outwear of the patients significance in standard of living, making appropriate treatment decisions; acquiesce with treatment and patients comfort.…”
mentioning
confidence: 99%
“…Cancer induces psychological trait that becomes a mark for grief and pain that is the reason why psychosocial oncology research studies indicated that a noteworthy percentage of cancer patients at all stages of the sickness has been oppress with psychological suffering. (2) However the psychological distress has the chances of interrupting the patient's quality of life and also influencing their option of treatments for cancer. (4) Internationally regimen of screening for distress is proposed as the compulsory standard for the good cancer care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to remember within the health field that patients experience a significant number of emotional reactions, which may include anxiety caused by fear of pain or uncertainty about the future, depression, problems of adaptation, etc [2]. This paper and other studies have evaluated the anxiety, depression, distress, and quality of life of patients in general and especially in patients who undergo diagnostic procedures or medical interventions [3].…”
mentioning
confidence: 99%